On the Origin of Neo-Sex Chromosomes in the Neotropical Dragonflies Rhionaeschna bonariensis and R. planaltica (Aeshnidae, Odonata) - Mola, Liliana Maria (2022)
Odonata have holokinetic chromosomes. About 95% of species have an XX/X0 sex chromosome system, with heterogametic males. There are species with neo-XX/neo-XY sex chromosomes resulting from an X chromosome/autosome fusion. The genus Rhionaeschna includes 42 species found in the Americas. We analyzed the distribution of the nucleolar organizer region (NOR) using FISH with rDNA probes in Rhionaeschna bonariensis (n = 12 + neo-XY), R. planaltica (n = 7 + neo-XY), and Aeshna cyanea (n = 13 + X0). In R. bonariensis and A. cyanea, the NOR is located on a large pair of autosomes, which have a secondary constriction in the latter species. In R. planaltica, the NOR is located on the ancestral part of the neo-X chromosome. Meiotic analysis and FISH results in R. planaltica led to the conclusion that the neo-XY system arose by insertion of the ancestral X chromosome into an autosome. Genomic in situ hybridization, performed for the first time in Odonata, highlighted the entire neo-Y chromosome in meiosis of R. bonariensis, suggesting that it consists mainly of repetitive DNA. This feature and the terminal chiasma localization suggest an ancient origin of the neo-XY system. Our study provides new information on the origin and evolution of neo-sex chromosomes in Odonata, including new types of chromosomal rearrangements, NOR transposition, and heterochromatin accumulation.